Discover Psychology 2.0 A Brief Introductory Text - Biswas-Diener, Robert; Diener, Ed; Open Textbook Library (Open Textbook Library, 2015)
This textbook presents core concepts common to introductory courses. The 15 units cover the traditional areas of intro-to-psychology; ranging from biological aspects of psychology to psychological disorders to social psychology. This book can be modified: feel free to add or remove modules to better suit your specific needs. Each module in this book is accompanied by instructor's manual, PowerPoint presentation, test items, adaptive student quiz, and reading anticipation guide. Please note that the publisher requires you to login to access and download the textbooks.
Intro to Psychology as a Science -- Research in Psychology -- Biology as the Basis of Behavior -- Developmental Psychology -- Sensation and Perception -- Consciousness -- Learning -- Memory -- Cognition, Language & Intelligence -- Emotion and Motivation -- Personality -- Psychological Disorders -- Therapies -- Social Psychology -- Psychological Health
In English.
Description based on online resource
Keywords: Social sciences -- Textbooks; Psychology -- Textbooks